Analysis of River Water Quality in Medan Belawan Regency based on the Diversity Index of Aquatic Insects as an Effort to Improve the Health of River Ecosystems from Heavy Metal Contamination (Ni) - Muhammad Taufik; Helen Gandaria Situmorang; Zul Alfian (Talenta Publisher, 2025)
Heavy metals are often found in river water polluted by industrial processes. To separate heavy metals from river water, blood clam shells (Anadara granosa) are used as adsorbents. This study aims to analyze the determination of Belawan river water pollution based on the Aquatic Insect Diversity Index and analyze the content of heavy metal (Ni) in waste by utilizing blood clam shell waste as an adsorbent. The method used is solid phase extraction. Based on the diversity index data, the condition of the Belawan River waters in the Control area is not polluted (H' 2.18), Settlement Area 1 is lightly polluted (H' 1.94), Settlement Area 2 is lightly polluted (H' 1.70), Industrial Area 1 is moderately polluted (H' 1.47), and Industrial Area 2 is lightly polluted (H' 1.7). The percentage of heavy metal (Ni) absorption in Residential Area 1, Residential Area 2, Industrial Area 1, and Industrial Area 2 were respectively 28.57%, 33.33%, 31.11%, and 34.38%. This shows that blood cockles (Anadara granosa) are able to absorb Ni metal up to 34.38%. Ni levels < 0.05 mg/L so it can still be used (PP No. 22 of 2021).